2021
DOI: 10.1371/journal.pone.0236231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous β-glucanase on ileal digesta soluble β-glucan molecular weight, digestive tract characteristics, and performance of coccidiosis vaccinated broiler chickens fed hulless barley-based diets with and without medication

Abstract: Introduction Limited use of medication in poultry feed led to the investigation of exogenous enzymes as antibiotic alternatives for controlling enteric disease. The objective of this study was to evaluate the effects of diet β-glucanase (BGase) and medication on β-glucan depolymerization, digestive tract characteristics, and growth performance of broilers. Materials and methods Broilers were fed hulless barley (HB) based diets with BGase (Econase GT 200P from AB Vista; 0 and 0.1%) and medication (Bacitracin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The CAZyme comparison analysis reflected that glucanase and glucosidase were more active in pigs with high finishing weights. Previous research has shown that glucanase supplementation could elevate the ratio of villi height to crypt depth, improve the absorption of nutrients, and finally promote body weight gain (Karunaratne et al, 2021). Furthermore, a greater abundance of glucosidase in the intestinal microbiome resulted in increased body weight gain in broilers (De Cesare et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The CAZyme comparison analysis reflected that glucanase and glucosidase were more active in pigs with high finishing weights. Previous research has shown that glucanase supplementation could elevate the ratio of villi height to crypt depth, improve the absorption of nutrients, and finally promote body weight gain (Karunaratne et al, 2021). Furthermore, a greater abundance of glucosidase in the intestinal microbiome resulted in increased body weight gain in broilers (De Cesare et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that β-mannanase can improve utilization of feed nutrients by reducing intestinal chyme viscosity and increasing carbohydrate utilization ( 24 , 25 ). Research has shown that β-glucanase effectively decreases levels of non-starch polysaccharides (NSPs) and crude fiber in wheat or barley diets ( 26 28 ). Similarly, the beneficial effects of xylanase on the growth performance of broilers have been widely reported ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%